The Role of Social Media in Indonesia’s Political Campaigns: A New Era of Electioneering - Assaefi, Amiluddin; Laskarwati, Batari; Zainurrohmah, Zainurrohmah (Indonesia Discourse, 2024)
This study investigates the transformative impact of social media on political campaigns in Indonesia. With the rapid digitalization of political discourse, social media has become a crucial tool for candidates to engage with voters, shape public opinion, and influence electoral outcomes. This research explores how platforms such as Facebook, Twitter, and Instagram have redefined traditional campaigning methods in Indonesia, fostering new dynamics in political communication, voter mobilization, and the dissemination of information. The study focuses on the increasing prominence of digital strategies in Indonesian elections, particularly during the 2014 and 2019 presidential campaigns. By analyzing campaign materials, social media posts, and public responses, this research highlights how political actors leverage online spaces to create narratives, challenge opponents, and interact directly with the electorate. It also examines the role of "influencers," online communities, and the viral spread of political content in shaping public discourse and opinion. This work contributes to the understanding of how digital media has reshaped the landscape of electoral politics, offering a deeper insight into the intersection of technology, democracy, and public participation in Indonesia. Moreover, it emphasizes the urgency of addressing challenges such as misinformation, digital divide, and the manipulation of online platforms to ensure the integrity of democratic processes. The research ultimately underscores the need for comprehensive strategies to regulate social media's role in elections while promoting transparent, inclusive, and fair political participation.